2020
DOI: 10.1051/e3sconf/202017217005
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor sorption dynamics in different compressions of eelgrass insulation

Abstract: Eelgrass shows potential in meeting the rising demands towards new, sustainable materials. It hosts a range of characteristics that benefits its application as a building material, such as thermal and acoustic insulating properties that can compete with conventional mineral wool insulation. However, as a porous bio-based building material, the moisture performance of eelgrass must be assessed to ensure its practical application. In this study, experimental investigations are conducted by a new automated vapor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…One can also find in Table 8 the GAB coefficients that are necessary to approximate the moisture content of the material based on the relative humidity. Despite that the GAB model is mainly applied for soil and food science, recent research has shown that it is applicable to building materials as well [45]. R 2 , the coefficient of determination of the GAB model compared to the moisture content measurement data is also included in the table.…”
Section: Moisture Sorption-desorption Capacity Measurementsmentioning
confidence: 99%
“…One can also find in Table 8 the GAB coefficients that are necessary to approximate the moisture content of the material based on the relative humidity. Despite that the GAB model is mainly applied for soil and food science, recent research has shown that it is applicable to building materials as well [45]. R 2 , the coefficient of determination of the GAB model compared to the moisture content measurement data is also included in the table.…”
Section: Moisture Sorption-desorption Capacity Measurementsmentioning
confidence: 99%
“…Due to its ability to store carbon and the fact that it may be recycled or biodegraded, it has a less negative impact on the environment [17]. Additionally, its hygrothermal properties also show even larger dynamics [18]. Biobased building materials (BBMs) may be an alternative option for CMs, according to research findings to date.…”
Section: Introductionmentioning
confidence: 99%